Studying the history of early English - Horobin, Simon (Perspectives on the English language., 2010)
"This accessible book introduces students to the latest linguistic approaches and methodologies for studying the history of English. Horobin shows the importance of thinking about why, as well as how, language changes over time and includes practical information on gathering evidence alongside worked-through textual examples"--Provided by publisher.